Geschlechterforschung in der Kritik - Casale, Rita; Rendtorff, Barbara; Andresen, Sabine; Moser, Vera; Prengel, Annedore (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2005)
The first yearbook of the Women's and Gender Studies Section of the German Society for Educational Science, entitled "Gender Studies in Criticism", is an account of the development of women's and gender studies to date in the context of educational science.